A Patterned Mechanochromic Photonic Polymer for Reversible Image Reveal. Issue 3 (23rd December 2019) - Zhang, Pei; Shi, Xiuyi; Schenning, Albert P. H. J.; Zhou, Guofu; de Haan, Laurens T.
Abstract: Mechanochromic photonic polymers, which can change structural color upon mechanical deformation, are promising for many applications including strain/stress sensors and security features. Here, a patterned poly(dimethylsiloxane) (PDMS)/cholesteric liquid crystal elastomer (CLCE) photonic mechanochromic bilayer film for reversible image reveal is reported, in which the PDMS component determines the mechanical properties and the CLCE determines the mechanochromic properties. The structural color pattern is achieved by locally crosslinking the CLCE layer at different temperatures using a photomask and utilizing the temperature response of the cholesteric liquid crystal main‐chain oligomers. The resulting PDMS/CLCE bilayer is able to reversibly reveal the predesigned invisible pattern upon stretching, showing that this method can be used to convey more advanced information to a potential user than would be possible with a simple homogeneous color change. It is also demonstrated that the bilayer film can be used as a stimuli‐responsive sticker able to detect bending deformations. Abstract : A patterned poly(dimethylsiloxane) (PDMS)/cholesteric liquid crystal elastomer (CLCE) photonic mechanochromic bilayer film for reversible image reveal is developed. The color pattern is achieved by locally crosslinking the CLCE layer at different temperatures using a photomask. The resulting bilayer can reversibly reveal an invisible pattern upon stretching, conveying more advanced information to a potential user a simple homogeneous color change would.